The Efficacy and Safety of Azithromycin for Patients with Cystic Fibrosis: A Systematic Review - Luh Adi Kusuma Suardiani; Fauna Herawati; Ni Made Suastini Suastini (Universitas Nahdlatul Ulama Surabaya, 2022)
Chronic inflammation of the lungs is a major cause of morbidity and mortality in patients with cystic fibrosis. One of the macrolides, azithromycin has antimicrobial, immunomodulatory, and anti-inflammatory effects that are useful in diseases with chronic inflammatory processes such as cystic fibrosis. This systematic review aimed to determine the efficacy and safety of azithromycin administration for cystic fibrosis patients in improving lung function. Pulmonary function was assessed by measuring the value of forced expiratory volume in one second (FEV1) in patients after intervention. The process of searching literature through PUBMED and Cochrane Library uses the keywords